Sex differences in progestogen- and androgen-derived neurosteroids in vulnerability to alcohol and stress-related disorders. (1st April 2021) - Peltier, MacKenzie R.; Verplaetse, Terril L.; Mineur, Yann S.; Gueorguieva, Ralitza; Petrakis, Ismene; Cosgrove, Kelly P.; Picciotto, Marina R.; McKee, Sherry A.
Abstract: Stress and trauma exposure disturbs stress regulation systems and thus increases the vulnerability for stress-related disorders which are characterized by negative affect, including major depressive disorder, anxiety disorders and posttraumatic stress disorder. Similarly, stress and trauma exposure results in increased vulnerability to problematic alcohol use and alcohol use disorder, especially among women, who are more likely to drink to cope with negative affect than their male counterparts. Given these associations, the relationship between stress-related disorders and alcohol use is generally stronger among women leading to complex comorbidities across these disorders and alcohol misuse. This review highlights the therapeutic potential for progestogen- and androgen-derived neurosteroids, which affect both stress- and alcohol-related disorders, to target the overlapping symptoms related to negative affect. This article is part of the special issue on 'Vulnerabilities to Substance Abuse.' Highlights: The relationship between stress-related disorders and alcohol use is stronger among women. Progestogen/androgen-derived neurosteroids underlie both alcohol/stress-related disorders. Allopregnanolone may reduce alcohol consumption through the reduction of negative affect.